Analisis Kemampuan Guru SDN 3 Puyung Dalam Mengelola Kelas Dengan Berbagai Macam Karakter Peserta Didik - Baiq Arnika Saadati; Melisa Wulandari (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the ability of teachers at SDN 3 Puyung to manage classes with diverse student characteristics. Classes consisting of students with different backgrounds, learning styles, and developmental levels require teachers to have effective and adaptive classroom management skills. This study used a descriptive qualitative approach, with data collection techniques through observation, semi-structured interviews, and documentation. The research subjects were teachers from grades 1 to 6 at SDN 3 Puyung. The results indicate that teachers at SDN 3 Puyung have implemented various classroom management strategies tailored to the characteristics of each student. The results indicate that teachers have good classroom management skills, employing a variety of learning methods, such as play and games, and utilizing learning media such as visual, audiovisual, and kinesthetic media. The use of varied media certainly allows teachers to reach all types of students' different learning styles. Teachers also employ an individualized approach to students with special needs. Teachers also group learning based on student ability and create an inclusive classroom atmosphere so that all students feel valued and actively engaged in the learning process. In addition, teachers try to maintain student motivation by giving positive rewards, reflecting on learning, and establishing good communication with students' parents.